2007
DOI: 10.1002/eat.20373
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the eating disorder examination‐questionnaire: Factor structure and internal consistency

Abstract: The results of this study provide support for the internal consistency of the EDE-Q and indicate a need for further examination of the factor structure of this instrument.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
291
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(332 citation statements)
references
References 18 publications
31
291
7
Order By: Relevance
“…The EFA and CFA with the EDE-Q items revealed a 12-item, 4-factor structure that did not replicate the original EDE-Q subscales. In fact, the four extracted factors were more comparable to those found by Peterson et al (19) with data from a community sample of women with bulimic symptoms. Both the current authors and Peterson et al (19) identified a similar body dissatisfaction/discomfort factor (which consisted of both Shape Concern and Weight Concern items), while both studies found that overvaluation of shape and weight loaded separately rather than with appearance concernrelated items.…”
Section: Discussionsupporting
confidence: 78%
“…The EFA and CFA with the EDE-Q items revealed a 12-item, 4-factor structure that did not replicate the original EDE-Q subscales. In fact, the four extracted factors were more comparable to those found by Peterson et al (19) with data from a community sample of women with bulimic symptoms. Both the current authors and Peterson et al (19) identified a similar body dissatisfaction/discomfort factor (which consisted of both Shape Concern and Weight Concern items), while both studies found that overvaluation of shape and weight loaded separately rather than with appearance concernrelated items.…”
Section: Discussionsupporting
confidence: 78%
“…Body dissatisfaction was operationalized by combining the Weight Concern and Shape Concern subscales (12 items total) to capture multiple aspects of body dissatisfaction. Furthermore, factor analytic work supports the items from these two subscales generally loading on one factor (Peterson et al, 2007). The EDE-Q subscales have good internal consistency (α=.78-.…”
Section: Eating Disorder Examination-questionnaire (Ede-q; Fairburn Andmentioning
confidence: 80%
“…Respondants rate 22 items using a 7-point frequency (0 = never; 6 = daily) and severity (0 = not at all; 6 = markedly) scale. The internal reliability of the measure is high (Cronbach's alpha = 0.90; see Peterson et al, 2007). The EDE-Q is widely with adults with eating disorders and has demonstrated validity in the assessment of adolescents with eating disorders (Binford and LeGrange, 2005).…”
Section: Eating Disorder Examination-questionnaire (Edeq)mentioning
confidence: 99%